Gender Dynamics in Three East Javanese Folk Tales - Raras Hafiidha Sari; Eko Hardinanto; Icha Fadhillasari; Yulianah Prihatin; Indah Mei Diastuti; Resdianto Permata Raharjo (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to describe gender dynamics in three East Javanese folktales. The method used in this study is a qualitative method with discourse analysis theory and a feminist approach. The data sources used are three folktales from East Java: Dewi Kilisuci, Dewi Sekartaji, and Ken Dedes. The data in this study are descriptions in the folktales related to gender dynamics. The results of the analysis show that female figures in the three tales are not merely passive objects in a patriarchal system, but also as subjects who have a strategic role in changing the direction of power and social values. Dewi Kilisuci displays spiritual and moral power, Dewi Sekartaji embodies political legitimacy through loyalty and cunning, while Ken Dedes represents symbolic power that became the foundation of the birth of a great dynasty. All three show that local mythology not only portrays the position of women in Javanese patriarchal culture, but also opens up space for resistance against male domination through images of purity, wisdom, and sacrifice. These findings are expected to enrich gender studies in regional literature and broaden understanding of symbolic politics in East Javanese oral tradition